Prevalence of work related musculoskeletal disorders (WMSDs) and ergonomic risk assessment among readymade garment workers of Bangladesh: a cross sectional study - Hossain, Md. Didar; Aftab, Afzal; Sarker, Malabika (PLOS ONE, 2018)
Background Work related Musculoskeletal Disorders (WMSDs) are one of the most common occupational diseases which mainly affects the lower back, neck and upper and lower extremities. The aim of this study was to determine prevalence of WMSDs in nine body regions among Ready Made Garment (RMG) workers in Bangladesh and ergonomics assessment of their exposure to risk factors for the development of WMSDs. Methods This cross-sectional study was conducted among 232 RMG employees (male: 46; female: 186; age: >18yrs) from nine RMG factories in Dhaka division during October 2015 to February 2016. Data were collected using a structured questionnaire consist of demographic questions, Nordic Musculoskeletal Questionnaire-Extended (NMQ-E) for WMSDs assessment in nine body regions and Quick Exposure Check (QEC) method for ergonomic assessment. Prevalence of WMSDs for each body region was determined. The association between WMSDs and ergonomic assessment of their exposure to risk factors were also analyzed. Results Respondents’ mean age was 31.3 years (SD = 7). Their mean Body Mass Index (BMI) was 23.51 kg/m2 (SD = 3.74). Among 186 female respondents, 46 reported lower back pain (24.7%) and 44 reported neck pain (23.7%). Among 46 male respondents, 10 reported neck pain (21.7%) while 6 reported knee pain (13%). Statistically significant relationship was found between twelve month WMSDs in anatomical region in elbows (p = 0.02), hips (p = 0.01), knees (p = 0.01) and ankle (p = 0.05) with age; upper back (p = 0.001), elbows (p = 0.001), wrists (p = 0.03), hips (p = 0.001) and ankles (p = 0.01) with job experience; hips with BMI (p = 0.03); elbows (p = 0.04) with daily working hour. QEC assessment showed that level of exposure to WMSDs risk was high among 80% of the study population (p<0.003). Conclusion The study found that lower back and neck were the most affected areas among RMG workers. Moreover, QEC findings warned the level of exposure to WMSDs risks is high and ergonomics intervention along with investigation and change to decrease exposure level is essential. Addressing musculoskeletal risk factors through ergonomic interventions in terms of working space, workers sitting/standing posture, seat and hand position during work and work-rest cycle are encouraged in RMG sector and policy makers.
Gesehen am 12.09.2019